Emotional Processing following Cortical and Subcortical Brain Damage: Contribution of the Fronto-Striatal Circuitry - Caterina Breitenstein; Irene Daum; Hermann Ackermann (Behavioural Neurology)
The present study examined the differential contribution of cortical and subcortical brain structures in emotional processing by comparing patients with focal cortical lesions (n = 32) to those with primarily subcortical dysregulation of the basal ganglia (Parkinson’s disease n = 14). A standardized measure of emotional perception (Tübingen Affect Battery) was used. Only patients in the more advanced stages of Parkinson’s disease and patients with focal damage to the (right) frontal lobe differed significantly from controls in both facial expression and affective prosody recognition. The findings imply involvement of the fronto-striatal circuitry in emotional processing.